Guiding Excellence: Examining the Nexus of Principal Leadership and Teaching Quality in Enhancing Students Learning in Pancasila and Citizenship Education - Dahlia Rineva Puspitasari; Luthfi Audia Pribadi; Diding Nurdin (AL-ISHLAH: Jurnal Pendidikan, 2024)
Education plays a pivotal role in developing human resources capable of addressing global challenges. This study explores the influence of school principal leadership and teacher teaching quality on student learning achievement, emphasizing their significance in fostering a supportive and effective learning environment. Despite existing research, gaps remain in understanding the interplay between leadership, teacher performance, and their combined effects on educational outcomes. A descriptive research design was employed, utilizing questionnaires and documentation to assess principal leadership, teacher teaching quality, and Civics learning achievement among Class XI students at SMA Negeri 5 Bandung for the academic year 2020/2021. Sampling involved 47 participants, and data analysis included normality tests, hypothesis testing, and regression analysis. Principal leadership exhibited a positive correlation with student learning achievement (r = 0.69, F = 26.74, p 0.05), while teacher teaching quality demonstrated an even stronger correlation (r = 0.83, F = 12.09, p 0.05). Combined, these factors significantly influenced student outcomes (F = 62.48, p 0.05), underscoring the synergistic effect of effective leadership and high-quality instruction. The findings emphasize the importance of leadership development and teacher professionalism in enhancing academic performance. Effective leadership fosters a conducive learning environment, while high-quality teaching directly impacts student success. The study highlights the critical roles of school principals and teachers in achieving quality education. Limitations include a small sample size and reliance on specific assessment tools. Future research should explore additional factors, incorporate larger samples, and adopt longitudinal and mixed-method approaches to provide deeper insights into educational effectiveness.